Visible-light-promoted divergent functionalizations of methylenecyclopropanes. Issue 22 (23rd September 2021) - Zhu, Baoxiang; Wang, Zhao; Xi, Hui; Feng, Zengqiang; Wang, Binglei; Jiao, Wenyang; Li, Zhongxian; Wang, Zechao; Wu, Junliang
Abstract : Visible-light-induced monofunctionalization and difunctionalization of MCPs via ring-opening and cyclization processes have been developed for the syntheses of difluoromethyl compounds, alkyl compounds, halides, and sulfonyl compounds. Abstract : Simple and convenient visible-light-promoted radical monofunctionalization and difunctionalization of methylenecyclopropanes via ring-opening and cyclization processes have been developed for the syntheses of difluoromethyl compounds, alkyl compounds, halides, and sulfonyl compounds in moderate to excellent yields. The methodologies feature a wide substrate scope and tolerate various functional groups. A possible radical mechanism has been investigated and proven as a single electron transfer (SET) procedure.